Mass Surveillance and Big Data Collection : No Way Around it? Societal Consequences and Oppression On the Scale - Hyvärinen, Julia (fi=Turun yliopisto|en=University of Turku|, 2017)
The research focuses on the collision of two constructs: mass surveillance and human rights. Mass surveillance is not a legal term, but refers to ubiquitous technology based surveillance, focusing mainly on metadata collection enabling creation of behavioural patterns and the surveillance of our everyday lives. The approach is general to the phenomenon as a whole, yet the territorial scope is within the EU and the U.S. jurisdictions. Since 2013 and the Snowden revelations the world discovered the magnitude of surveillance practices conducted by the NSA. This led to an eye-opening discovery of a global mass surveillance scheme with extensive technological measures and tools to ‘spy on citizens’. Mass surveillance is mainly justified in the name of security, it is practiced to battle terrorism and other criminal activities. Yet it is also practiced by corporations mainly to their own count, yet allowing governments to expand their practices to private sector with intelligence co-operation. Mass surveillance conflicts with very essential parts of our lives such as privacy, freedom of expression and anonymity, leading to versatile societal complexities from behavioural misconducts to enabling coercion, discrimination, false positives and manipulation to name a few, leading to an overall defeat in democracy and the liberties provided under democratic societies, resulting in a form of oppression. The legal sociological approach allows the phenomenon study of the consequences as a whole, as well as the overview on individuals’ attitudes regarding surveillance practices with interdisciplinary perspectives. In addition an evaluation of the effectiveness of mass surveillance practices in fighting terrorism is provided via descriptive and interpretational methods. The results evidently point to a direction of ineffectiveness in terrorism detection, as the magnitude of data collection overweighs the human intermediary resources, important to the detection process. Which directs to the point of mass surveillance practices not being justifiable in the name of the original intent of providing security and safety.

Tutkielma tarkastelee massavalvonnan ja ihmisoikeuksien välistä kollisiota. Massavalvonta itsessään ei ole lainopillinen termi, sitä kuitenkin käytetään yleisesti kuvaamaan ilmiötä, joka koostuu kaikkialla olevasta teknologia perusteisesta valvonnasta, kohdistuen metatiedon keruuseen, siitä analysoitavaan käyttäytymismallien muodostumiseen sekä jokapäiväisen elämän valvomiseen. Lähtökohta ilmiön tutkimiseen on yleinen, kuitenkin kohdistaen territoriaalisen ulottuvuuden EU:n sekä US:n lainkäyttöalueisiin. Vuoden 2013 Snowdenin paljastusten jälkeen, maailmalle levisi tieto NSA harjoittamasta massavalvonnasta ja sen globaalista ulottuvuudesta, paljastaen laajojen teknologisten infrastruktuurien mahdollistaman kansalaisten valvonnan. Massavalvontaa perustellaan terrorismin kytkemisen kannalta ehdottomana keinona, vaikka valvontaa harjoittavat myös yksityisen sektorin toimijat, pääosin omaan lukuunsa, mutta myös yhteistyössä valtioiden tiedustelupalveluiden kanssa. Massavalvonta toimintatapana sotii vasten ihmis- ja perusoikeuksiamme, läpäisten yksityisyydensuojan, sananvapauden sekä anonymiteetin, johtaen monialaisiin yhteiskunnallisiin ongelmiin aina yksilön käyttäytymishäiriöistä muun muassa pakottamiseen, syrjintään sekä manipulaatioon, sortaen demokraattisen yhteiskunnan perusvapauksia ja arvoja. Tutkimussuunta on oikeussosiologinen tutkien kahden ilmiön välistä vuorovaikutussuhdetta sekä ihmisten asenteita massavalvontaa koskien, sisältäen poikkitieteellisiä metodeja. Lisäksi tutkimus sisältää massavalvonnan tehokkuusarvioinnin deskriptiiviseltä ja tukinnalliselta kannalta, sillä varsinaisia tilastoja ei ole saatavilla. Tulokset melko selkeästi viittaavat massavalvonnan tehottomuuteen terrorismin estämisessä, johtuen valtavasta kerätystä tietomäärästä, jolloin resurssien kohdentaminen kaiken tiedon analysoimiseen on mahdotonta. Tämä puolestaan viittaa siihen, että turvallisuuden nimissä oikeutetulla massavalvonnalla ei ole mitään perusteita.